2010
DOI: 10.1007/s00432-009-0746-6
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET and other imaging modalities for the evaluation of breast cancer recurrence and metastases: a meta-analysis

Abstract: Background and purposeBreast carcinoma is the most common cancer in female patients with a propensity for recurrence and metastases. The accuracy of ultrasound (US), computed tomography (CT), magnetic resonance imaging (MRI), scintimammography (SMM) and positron emission tomography (PET) in diagnosing the recurrent and/or breast cancer has never been systematically assessed, and present systematic review was aimed at this issue.MethodsMEDLINE and EMBASE were searched for articles dealt with detection of recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 77 publications
1
30
0
2
Order By: Relevance
“…In the study by Schmidt et al, PET/CT was found to be more sensitive than WB MRI for the detection of lymph node involvement (n 5 21 vs. n 5 16); however, WB MRI was slightly more sensitive (n 5 154 vs. n 5 147) for the detection of distant metastases (26). Two metaanalyses compared 18 F-FDG PET/CT, conventional imaging (ultrasonography, CT, and bone scintigraphy), and MRI for the detection of breast cancer recurrence (48,49). PET/CT outperformed PET alone and conventional imaging but not MRI.…”
Section: Pet/ct In Restaging Of Breast Carcinomamentioning
confidence: 99%
“…In the study by Schmidt et al, PET/CT was found to be more sensitive than WB MRI for the detection of lymph node involvement (n 5 21 vs. n 5 16); however, WB MRI was slightly more sensitive (n 5 154 vs. n 5 147) for the detection of distant metastases (26). Two metaanalyses compared 18 F-FDG PET/CT, conventional imaging (ultrasonography, CT, and bone scintigraphy), and MRI for the detection of breast cancer recurrence (48,49). PET/CT outperformed PET alone and conventional imaging but not MRI.…”
Section: Pet/ct In Restaging Of Breast Carcinomamentioning
confidence: 99%
“…During the follow-up care, survivors' psychological needs were often neglected (Park and Hwang, 2012). A main theme of depression among breast cancer survivors was the fear of breast cancer recurrence and metastasis (Pan et al, 2010). Long term effects associated with chemotherapy include infertility, sexual dysfunction, menopause-associated health problems e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Bu nedenle PET, difüzyon ağırlıklı ve perfüzyon MR görüntülemeden elde edilen sayısal parametrelerin, geleneksel kontrastlı meme MR'ı tamamlayıcı nitelikte bilgiler vermesi önem taşımaktadır. Hastalık rekürrensinin değerlendirilmesinde ise, yayımlanan bir metaanalize göre PET ve tüm vücut MR görüntüleme, ultrasonografi (USG) ve BT'ye üstündür (59). Hastalığın yeniden evrelenmesinde, lenf nodu tutulumunun değerlendirilmesinde FDG PET/BT daha yüksek duyarlılığa sahipken, tüm vücut MR görüntüleme daha fazla sayıda kemik, karaciğer ve beyin metastazı saptayabilmektedir (48).…”
Section: Memekanserivepet/mrunclassified